Automatic Face Detection and Attendance of Class Students - Azhee Wria Muhamad; Luqman Mohammed Mustafa; Ari Sabir Arif (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Taking attendance within the schools and colleges are being a squander of time and exertion for both the students and courses. Presently days biometric are more utilitarian, they have fingerprint recognition, facial recognition iris filtering recognition voice recognition signature recognition. The attendance system checking as a comparison of manual call and involves a lot of paperwork, making it difficult to look for any information and perform modifications on the student. In the system, there's a parcel of scope for intermediary attendance. To solve this situation, the proposed system has automated the attendance marking prepare by using the Viola-Jones Algorithm face detection technologies. The study presents a modern model in automatic participation organized the system, expanded with computer vision algorithms. The attendance system after detecting all students face and it should be applied some filter on the image to enhancement, face detect and remove the noise on images when capturing all face. This requires a high-end determination of a system in arranging to get the way better results. So, this may run as it were a big database and compare them with the face required. The equipment promises to offer precise comes about and some more explanations announcing system that appears understudy movement and the presents in a class.